Emission Reduction Performance of Modified Hot Mix Asphalt Mixtures - Chaohui Wang; Qiang Li; Kevin C. P. Wang; Xiaolong Sun; Xuancang Wang (Advances in Materials Science and Engineering)
Three novel asphalt modifiers with pollutant emission reduction effects and new emissions measurement equipment compatible with several preexisting asphalt production systems are developed in this paper. The effects of various modifier, asphalt binder type, and gradation of hot mix asphalt (HMA) on pollutant emissions are evaluated in the lab through a comprehensive experimental design. Furthermore, road performances are monitored to evaluate the emissions reduction of modified HMA mixture for production. With increasing modifier content, the emissions reduction performance is improved markedly, with maximum reduction of 70.5%. However, the impact of modifier content on pollutant emissions reduction tends to be insignificant for dosages greater than 20% of the initial asphalt weight. Changes in asphalt type and asphalt mix gradation are found to moderately impact the emissions reduction effect. Finally, the mechanisms of emissions reduction are investigated, primarily attribute to their physical and chemical adsorption and pollutant reductive degradation characteristics.